0746 Adolescent Girls are Less Likely than Boys to have SDB and Elevated Blood Pressure, but More Likely to have Orthostatic Hypertension: Penn State Child Cohort. (27th April 2018) - Bixler, E O; He, F; Fernandez-Mendoza, J; Liao, D; Calhoun, S; Criley, C; Cain, P; Vgontzas, A
Abstract: Introduction: New guidelines have just been established for elevated blood pressure (BP) in adolescents. The purpose of this study was to establish the association of SDB with elevated BP controlling for relevant risk factors in 421 adolescent subjects evaluated in our representative population sample. Methods: All subjects had their BP measured in the evening before their sleep study. BP was assessed in both the seated and supine position 3 times following a rest period of 5 minutes. The average of the final 2 measurements was evaluated. Standing BP was assessed 2 times immediately after standing and averaged. Orthostatic BP was defined as the standing minus the supine average pressures. The definition of elevated BP, based on the new guidelines, included the thresholds for: elevated BP; stage1 and stage 2 hypertension. SDB was defined as three groups (AHI<2, 2<AHI<5, and AHI>5). Results: Adolescent girls were less likely to have SDB than boys (p<0.001) as has been observed in adults. Adjusting for age, minority, gender, and z (visceral fat), there was an independent dose-response relationship between 2<AHI<5 (OR=1.5) and AHI>5 (OR=2.3) and elevated BP, with a significant dose-response relationship (p=0.03). Male (OR=4.1) and visceral fat (OR=1.4) were also significant contributing risk factors for elevated BP in this model. SDB was not associated with orthostatic hypotension. However, orthostatic hypertension was associated with 2<AHI<5 (OR=1.3) and AHI>5 (OR=2.9), with a significant dose-response relationship (p=0.05). Female (OR=2.0) and visceral fat (OR=1.5) were additional significant risk factors for orthostatic hypertension. Conclusion: SDB is associated with both elevated BP and orthostatic hypertension in a dose-response manner. Adolescent girls are less likely than boys to have SDB as well as elevated BP, but more likely to have orthostatic hypertension. Visceral fat appears to be a common risk factor for both elevated BP and orthostatic hypertension. Support (If Any): NIH R01 HL097165, C06 RR016499, NCATS UL1TR000127.